From soil intelligence to “Made-in-Rwanda” fertiliser blends: The journey of RAB and CGIAR Sustainable Farming Program through CIP - International Potato Center (2025)
This blog documents Rwanda’s transition from generic fertilizer recommendations to data-driven, site-specific nutrient management based on soil intelligence. Through collaboration between the Rwanda Agriculture and Animal Resources Development Board (RAB), the CGIAR Sustainable Farming Program, and CIP, soil analysis and digital tools were translated into locally produced “Made-in-Rwanda” fertilizer blends. The initiative demonstrates how evidence-based fertilization, local manufacturing, and strong institutional partnerships can improve soil health, increase productivity, and support more resilient and sustainable agrifood systems.